Local oscillator phase noise model for EVM estimation and optimization - Fialho, Vitor (2017)
This work presents a local oscillator (LO) phase noise model and its experimental validation for carrier to phase noise ratio (CPNR) and error vector magnitude (EVM) evaluation on a radio frequency (RF) transceiver. The proposed LO model is based on a type II charge pump phase locked loop with a combined phase noise source from the voltage controlled oscillator and input reference with a low pass characteristic. The obtained results of CPNR and signal to phase noise ratio are based on numerical simulations and validated with experimental measurements based on a commercial RF transceiver chip. The EVM of the transmitted RF channel is also measured and compared with CPNR.